2015
DOI: 10.15403/jgld.2014.1121.mlp
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Controlled Attenuation Parameter Measured by Transient Elastography for the Non-invasive Assessment of Liver Steatosis: a Prospective Study

Abstract: Background & Aims: A novel non-invasive tool based on the evaluation of ultrasound attenuation using transient elastography (TE) has been developed, called controlled attenuation parameter (CAP). We aim to establish the histopathological parameters that significantly influence CAP, the cutoff values and their performance in predicting each steatosis grade on a group of biopsied patients with chronic liver diseases (CLD) from Romania.Methods. We prospectively analyzed 201 consecutive CLD patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 47 publications
1
33
1
2
Order By: Relevance
“…For this reason, CAP by FibroScan evolved to be a reference method in the last years. Several studies demonstrated that the accuracy of CAP in comparison with liver biopsy is higher than 80% [21,22], and this is quite enough for daily practice. The introduction of CAP on both M and XL probes of FibroScan increased the feasibility of the method [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, CAP by FibroScan evolved to be a reference method in the last years. Several studies demonstrated that the accuracy of CAP in comparison with liver biopsy is higher than 80% [21,22], and this is quite enough for daily practice. The introduction of CAP on both M and XL probes of FibroScan increased the feasibility of the method [23].…”
Section: Discussionmentioning
confidence: 99%
“…Published data show that the prevalence of NAFLD varies between 42.6 and 69% in T2DM patients [20,21], while a previous study from our area showed a prevalence of NAFLD in T2DM patients of up to 87.1% [22]. The prognosis of these patients is different if they present only simple steatosis-non-alcoholic fatty liver (NAFL)-or if they have already developed NASH, early NASH (no or mild fibrosis), fibrotic NASH (significant/advanced fibrosis), or NASH cirrhosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Because this was not a liver-biopsy proven study, we could not assess alterations in hepatic inflammation and hepatocellular ballooning following treatment. Regarding CAP, previous studies have analyzed the association of CAP values with liver histology, particularly in NAFLD patients with high-grade steatosis and elevated BMI, and have verified the utility of CAP as a non-invasive tool for diagnosing and monitoring NAFLD patients (27)(28)(29)(30). However, despite its relatively high accuracy in detecting hepatic steatosis, the agreement between histologic analysis and CAP in hepatic fat quantification varies among individuals with mild steatosis (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, these are costly and some are not easily available, not standardized, or have controversial performance [6]. Recently, the controlled attenuation parameter (CAP) was developed and demonstrated good accuracy for the detection and quantification of steatosis in patients with chronic liver disease from various etiologies [7, 8]. Furthermore, CAP is measured simultaneously with liver stiffness (LS) using transient elastography (TE) [2, 9].…”
Section: Introductionmentioning
confidence: 99%